Desempenho e estratégia de movimento de adolescentes com hemiplegia espástica e com desenvolvimento normal em tarefa de precisão: influência de constraints da tarefa, do indivíduo e do suporte contextual - Priscilla Rezende Pereira Figueiredo (2014)
When teenagers with hemiplegic cerebral palsy (CP) are compared to typically developing (TD) teenagers during the execution of upper limb tasks, worse performance and atypical movement strategies presented by the former are usually attributed to the presence or severity of their neural damage. We aimed to verify the influence of other factors, such as task accuracy demands, contextual support and individuals skills, that could be underlying the differences between teenagers with and without spastic hemiplegia during a reciprocal aiming task. Twenty participants (nine with hemiplegic CP and 11 with typical development) used a pointer to continuously hit two targets with maximum speed and accuracy. Task conditions were manipulated by changing the targets size; by modifying the pointers adequacy for precision tasks; and by switching between individuals preferred/non-affected and non-preferred/affected upper limbs. The results point to a strong influence of the experimental manipulations on the behavior of both teenagers with and without CP. Even though hemiplegic teenagers exhibited worse performance compared to TD teenagers, the magnitude of the differences was more pronounced when the capability/demand relation was more dissimilar between those individuals. Regarding movement strategies, teenagers with hemiplegia, compared to those with typical development, presented lower magnitude of elbow movements and increased magnitude of shoulder movements when performing the task with their less skilled upper limb. However, in spite of those differences, hemiplegic and TD teenagers showed comparable increases in trunk involvement when facing more challenging task conditions, which highlights similarities in the behavior of individuals with and without CP in face of increases in task demands. We propose reasons as to why such strategies were implemented and conclude that they reflect a necessary adaptation to the conditions under which the task is performed, given the individuals capabilities, and not a primarily pathological manifestation.